Salmonella antimicrobials inherited and the non-inherited resistance: mechanisms and alternative therapeutic strategies - Zhou, Kaixiang; Sun, Lei; Zhang, Xuehua; Xu, Xiangyue; Mi, Kun; Ma, Wenjin; Zhang, Lan; Huang, Lingli (Frontiers in Microbiology, 2023)
Salmonella spp. is one of the common foodborne pathogens. Typhoid fever and enteritis caused by Salmonella enterica are associated with 16~33 million infections and 500,000 to 600,000 deaths annually worldwide. The eradication of Salmonella is becoming increasingly difficult because of its remarkable capacity to counter antimicrobial agents. In addition to the intrinsic and acquired resistance of Salmonella, increasing studies indicated that the tolerant cells (non-inherited, temporary), including biofilms and persister cells, plays a critical role in refractory infections and resistance evolution. These remind the urgent demand for new therapeutic strategies against Salmonella. This review starts with escape mechanisms of Salmonella against antimicrobial agents, with particular emphasis on the roles of tolerant cells in antibiotics failure and resistance evolution. Then drug design or therapeutic strategies that shows impressive effects in overcoming Salmonella resistance are summarized completely, such as overcoming the barrier of outer membrane by targeting MlaABC system, reducing tolerant cells by limiting hydrogen sulfide, and applying probiotics or predatory bacteria, as well as according to the clinical practice, the advantages and disadvantages of above strategies are discussed. Finally, we further analyze how to deal with the tricky problems that can promote these novel strategies to be applied in the clinic.